In vitro exposure of pig neonatal isletlike cell clusters to human blood - Nagaraju, Santosh; Bertera, Suzanne; Tanaka, Takayuki; Hara, Hidetaka; Rayat, Gina R.; Wijkstrom, Martin; Ayares, David; Trucco, Massimo; Cooper, David K. C.; Bottino, Rita (Xenotransplantation (Københaven), 2015)
Background Pig islet grafts have been successful in treating diabetes in animal models. One remaining question is whether neonatal pig isletlike cell clusters (NICC) are resistant to the early loss of islets from the instant blood‐mediated inflammatory reaction (IBMIR). Methods Neonatal isletlike cell clusters were harvested from three groups of piglets—(i) wild‐type (genetically unmodified), (ii) α1,3‐galactosyltransferase gene‐knockout (GTKO)/CD46, and (iii) GTKO/CD46/CD39. NICC samples were mixed with human blood in vitro, and the following measurements were made—antibody binding; complement activation; speed of islet‐induced coagulation; C‐peptide; glutamic acid decarboxylase (GAD65) release; viability. Results Time to coagulation and viability were both reduced in all groups compared to freshly drawn non‐anticoagulated human blood and autologous combinations, respectively. Antibody binding to the NICC occurred in all groups. Conclusions Neonatal isletlike cell clusters were subject to humoral injury with no difference associated to their genetic characteristics.